(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Mayer-Rokitansky-Küster-Hauser syndrome is a congenital abnormality that affects the uterus and the upper two-third of the vagina. It is expected to affect 1 in every 5000 live births. The syndrome is characterized by aplasia of the Müllerian duct (uterus and upper two-third of the vagina) in a person with karyotype 46, XX with female phenotype characteristic of primary amenorrhea in adolescence. But some people present with other complaints such as infertility, dyspareunia, or periodic pain. There are two types of Mayer-Rokitansky-Küster-Hauser syndrome: typical (isolated uterovaginal aplasia) and atypical (associated with extragenital symptoms). Renal, bone, ear, and heart abnormalities are examples of extragenital anomalies. Case: We are hereby presenting the case of a 26 year old female brought for medico legal autopsy. On careful examination of genital organs, the incidental finding of MRKH syndrome was observed. Conclusion: In every case, it is important to review the deceased’s medical history, psychological condition before death by speaking with family members and friends, and to examine each and every organ during the autopsy. Else, rare incidental findings may go unnoticed.